Simulating the efficacy of wolf-dog hybridization management with individual-based modeling - Santostasi, Nina Luisa (Conservation biology : the journal of the Society for Conservation Biology, 2024)
© 2024 The Author(s). Conservation Biology published by Wiley Periodicals LLC on behalf of Society for Conservation Biology.